Impact of a targeted isolation strategy at intensive-care-unit-admission on intensive-care-unit-acquired infection related to multidrug-resistant bacteria: a prospective uncontrolled before–after study. (October 2016) - Ledoux, G.; Six, S.; Lawson, R.; Labreuche, J.; Blazejewski, C.; Wallet, F.; Duhamel, A.; Nseir, S.
Abstract: Isolation of patients with multidrug resistant (MDR) bacteria is recommended to reduce cross-transmission of these bacteria. However, isolation of critically ill patients has several negative side effects. Therefore, we hypothesized that a targeted isolation strategy, based on the presence of at least one risk factor for MDR bacteria, would be not inferior to a systematic isolation strategy at intensive-care unit (ICU) admission. This prospective before–after study was conducted in a mixed ICU, during two 12-month periods, separated by a 1-month 'wash-out' period. During the before period, isolation was systematically performed in all patients at admission. During the after period, isolation was only performed in patients with at least one risk factor for MDR bacteria at admission. During the two periods, routine screening for MDR bacteria was performed at ICU admission, and isolation prescription was modified after receipt of screening result. Primary outcome was the percentage of patients with ICU-acquired infection (ICUAI) related to MDR bacteria, measured from ICU admission until ICU discharge or day 28, whatever happens first. A total of 1221 patients were included. No significant difference was found in ICUAI related to MDR bacteria (85 of 585 (14.5%) vs. 84 of 636 (13.2%) patients, risk difference, −1.3%, 95% confidence interval [−5.2 to 2.6%]) between the two periods, confirming the non-inferiority hypothesis. Our results suggest that targeted isolation of patients at ICU admission is not inferior to systematic isolation, regarding the percentage of patients with ICUAI related to MDR bacteria. Further randomized controlled multicentre studies are needed to confirm our results.